Maladaptive Pulmonary Vascular Responses to Chronic Sustained and Chronic Intermittent Hypoxia in Rat - Jesus Prieto-Lloret; Elena Olea; Ana Gordillo-Cano; Inmaculada Docio; Ana Obeso; Angela Gomez-Niño; Philip I. Aaronson; Asuncion Rocher (MDPI AG, 2021)
Chronic sustained hypoxia (CSH), as found in individuals living at a high altitude or in patients suffering respiratory disorders, initiates physiological adaptations such as carotid body stimulation to maintain oxygen levels, but has deleterious effects such as pulmonary hypertension (PH). Obstructive sleep apnea (OSA), a respiratory disorder of increasing prevalence, is characterized by a situation of chronic intermittent hypoxia (CIH). OSA is associated with the development of systemic hypertension and cardiovascular pathologies, due to carotid body and sympathetic overactivation. There is growing evidence that CIH can also compromise the pulmonary circulation, causing pulmonary hypertension in OSA patients and animal models. The aim of this work was to compare hemodynamics, vascular contractility, and L-arginine-NO metabolism in two models of PH in rats, associated with CSH and CIH exposure. We demonstrate that whereas CSH and CIH cause several common effects such as an increased hematocrit, weight loss, and an increase in pulmonary artery pressure (PAP), compared to CIH, CSH seems to have more of an effect on the pulmonary circulation, whereas the effects of CIH are apparently more targeted on the systemic circulation. The results suggest that the endothelial dysfunction evident in pulmonary arteries with both hypoxia protocols are not due to an increase in methylated arginines in these arteries, although an increase in plasma SDMA could contribute to the apparent loss of basal NO-dependent vasodilation and, therefore, the increase in PAP that results from CIH.